PENGARUH EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER), TINGKAT INFLASI DAN TINGKAT SUKU BUNGA TERHADAP RETURN SAHAM - Very Budiyanto; M. Agus Salim; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study was to determine the effect of variable earning Per Share (EPS), Debt to Equity Ratio (DER), Inflation and Interest Rate on Stock Return partially. The population used in this study is a Food and Beverages listed on the Stock Exchange during the period 2013-2016 totaling 15 companies. Mechanical sampling using purposive sampling, data analysis methods used in this research is multiple linear regression analysis.The results of this study provide empirical evidence that the variability Earning Per Share (EPS), Debt to Equity Ratio (DER), and the rate of interest has no significant effect on stock returns. While the Inflation has a significant effect on stock returns. Keywords: EPS, DER, Interest Rate, Inflation Rate, Stock Return.